Propuesta de mejora a los procesos de escritura de libros y artículos científicos de la ESPAM MFL. - Montesdeoca Muñoz, Denisse Alicia (2017)
The research was carried out with the aim of proposing improvements to the subprocesses: Follow-up of Teaching Publication (Teaching Planning, Monthly Report, Receipt of Article), Undergraduate Article, Publication in the Magazine ESPAMCIENCIA, and Publication of Books, with the purpose of optimizing times in these subprocesses. The research was carried out in three stages: The first one was the information retrieval in the General Coordination of Research (CGI) of the ESPAM MFL, where the necessary information was obtained from the representation of the subprocesses through the AS IS diagram. The second stage made possible the Value Added Analysis, the determination of the time taken by each activity, and analyzed which activities could be combined, improved or eliminated. The third stage made recommendations for improvements to the subprocesses and processes under analysis for the sake of fluidity, effectiveness, and efficiency. Once the mentioned steps were applied, the optimization of the activities that in one way or another added value to the subprocesses was obtained. This is why it is concluded that the application of AVA allowed proposing improvements to the processes with the purpose of speeding the execution of the same.